2019
DOI: 10.1371/journal.pone.0221680
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of black cumin on the formation of heterocyclic aromatic amines in meatball

Abstract: The impact of black cumin usage on some qualitative properties and formation of heterocyclic aromatic amines (HAAs) in meatball production was investigated. It was found that black cumin usage rate, cooking process and temperature had a significant effect (p<0,01) on the water content, pH, and thiobarbituric acid reactive substances (TBARS) values of meatballs. On the other hand, black cumin usage significantly (p<0,01) reduced the water content and cooking loss. The water content and cooking loss of the meatb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 64 publications
(122 reference statements)
3
33
0
Order By: Relevance
“…10 According to how they are generated, HCAs are generally divided into two classes: the aminoimidazo-azaarenes (IQ-types), and the amino-carbolines (non-IQ-types). The former are produced via the reaction of amino acids, glucose, creatine or creatinine when heated, through the Maillard reaction, while the latter are induced by the pyrolysis of amino acids/proteins when heated to temperatures above 300 C. 11 Among them, PhIP is classied as a Group 2B carcinogen by the International Agency for Research on Cancer (IARC); the b-carbolines (harman and norharman) have been shown to be co-mutagenic because they promote the genotoxicity of mutagenic aromatic amines. 2,10 These three HCAs, namely PhIP, harman and norharman, are relatively common in fried chicken.…”
Section: Introductionmentioning
confidence: 99%
“…10 According to how they are generated, HCAs are generally divided into two classes: the aminoimidazo-azaarenes (IQ-types), and the amino-carbolines (non-IQ-types). The former are produced via the reaction of amino acids, glucose, creatine or creatinine when heated, through the Maillard reaction, while the latter are induced by the pyrolysis of amino acids/proteins when heated to temperatures above 300 C. 11 Among them, PhIP is classied as a Group 2B carcinogen by the International Agency for Research on Cancer (IARC); the b-carbolines (harman and norharman) have been shown to be co-mutagenic because they promote the genotoxicity of mutagenic aromatic amines. 2,10 These three HCAs, namely PhIP, harman and norharman, are relatively common in fried chicken.…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic aromatic amines (HAAs) are also formed during cooking of proteinaceous foods (Oz, 2019). So far, more than twenty‐five different HAAs have been identified in heat‐treated cooked foods (Oz, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, bouillons can be produced from various types of meat, such as chicken, beef, pork with no standard time and temperature. Vegetables and spices can be incorporated depending upon the product type (Dolara et al ., 1979; Oz, 2019). On the other hand, material variation can lead to variation in the amount of HAA.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown a positive correlation between pancreas, breast, colorectal, prostate and ureter cancers and high red meat consumption (Klassen et al ., 2002). To date, more than twenty‐five HAAs have been isolated and identified in heat‐treated foods (Oz, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation